"Harlem Knows": Eleo Pomare's Choreographic Theory of Vitality and Diaspora Citation in Blues for the Jungle. Issue 3 (December 2020) - Wells, Charmian
Abstract : This article examines Eleo Pomare's concept of vitality in his piece Blues for the Jungle (1966) as a black aesthetic approach to choreography. Vitality seeks to connect with black audiences in Harlem by referencing and affirming shared cultural knowledge, conveying an embodied epistemology of the US political economy defined by the lived experiences of Harlem: "Harlem knows." Using a lens of diaspora citation, I argue that Pomare's choreographic citations of "vital" ways of moving and knowing in Harlem critique the terms for "proper" national belonging, while articulating diasporic belonging in motion.